RoAp stars: surface lithium abundance distribution and magnetic field configuration. Issue Volume 9:Issue S302(2013) (7th August 2014) - Polosukhina, N.; Shulyak, D.; Shavrina, A.; Lyashko, D.; Drake, N. A.; Glagolevski, Yu.; Kudryavtsev, D.; Smirnova, M.
Abstract: High-resolution spectra obtained with the 6m BTA telescope, Russia, and with HARPS and VLT/UVES telescopes at ESO, Chile, were used for Doppler Imaging analysis of two roAp stars, HD 12098 and HD 60435, showing strong and variable Li resonance line in their spectra. We found that Li has highly inhomogeneous distribution on the surfaces of these stars. We compared our results with previously obtained Doppler Imaging mapping of two CP2 stars, HD 83368 and HD 3980, and discuss the correlation between the position of the high Li-abundance spots and magnetic field.